Trusted Computing - Chen, Liqun (Springer, 2017)
This book constitutes the refereed proceedings of the Second International Conference on Trusted Computing, TRUST 2009, held in Oxford, UK, in April 2009. The 15 revised full papers presented were carefully selected during two rounds of reviewing and improvement from an initial total of 33 submissions. The papers cover the core issues of trust in IT systems and present current research, devoted to technical aspects of trusted computing. The papers are organized in topical sections on implementation of trusted computing, attestation, PKI for trusted computing, applications.